MODEL PEMBELAJARAN M-APOS TERINTEGRASI KARAKTER TERHADAP KEMAMPUAN REPRESENTASI MATEMATASIS SISWA SD - Nurmitasari Nurmitasari; Ajeng Dwi Puspitasari; Lisa Indriani; Muhana Sabina; Riski Putri Nurcahayani; Muhammad Afif Jidan (LPPM Universitas Cipta Mandiri, 2026)
This study aims to determine the effect of the M-APOS (Modification–Action–Process–Object–Schema) learning model integrated with character education on elementary school students’ mathematical representation ability. The research was motivated by the low ability of students to express mathematical ideas through various forms of representation, including visual, symbolic, and verbal. The study employed a quantitative approach with a Quasi-Experimental method using The Nonequivalent Control Group Design. The sample consisted of two classes: the experimental class implementing the M-APOS model integrated with character values and the control class using conventional learning. The instrument used was an essay test on mathematical representation ability, validated and tested for reliability. The results showed a significant difference between the experimental and control classes, with the calculated t-value exceeding the table value at a 0.05 significance level. The average representation ability of students in the experimental class reached 88.05%, categorized as very high. These findings indicate that the M-APOS model integrated with character education effectively improves students’ mathematical representation skills while fostering positive character values such as responsibility, cooperation, and honesty. Therefore, this model can serve as an innovative and relevant learning strategy for mathematics education in elementary schools.